Clinical effect of platelet-rich fibrin layering on peri-implant keratinized tissue - A. M. Kurukchi; A. S. Al-Radha; A. A. Mahmood (Regulatory Mechanisms in Biosystems, 2025)
P eri-implant tissues are very important for the long-term stability of dental implants. Sufficient width of keratinized tissue has been associated with lower levels of plaque formation, and reduced inflammation of the gingiva. Greater thickness of soft tissue has also been associated with less bone resorption. There is evidence that supports the notion that platelet-rich fibrin (PRF) can be used in enhancing the healing and regeneration of soft tissue. The primary objective of this study wa s to evaluate the effect of different numbers of PRF membrane layers on the thickness and width of keratinized tissue around dental implants during the early heal ing phase. Fifteen participants per group (N = 45) were sequentially assigned to one of three groups: single PRF membrane group, multiple PRF membrane group, and control group. A standardized two-stage implant placement proc e dure was performed . The outcomes included the estimation of keratinized tissue width (KTW) and thickness (KTT). The m e a surements were recorded preope ratively and six and twelve weeks postoperatively. The use of PRF either as a single me m brane or in three layers did not cause any significant increase in the keratinized tissue width at the postoperative 6-week or 12-week time points. At the same time, t he single and multiple PRF groups had significantly greater increases in the thickness of cre stal and buccal soft tissue compared with the control group at 12 weeks. Platelet-rich fibrin had minimal effect on the kerat i nized tissue width . However, its application , particularly in three layers, significantly enhanced the thickness of buccal and crestal tissue s .